Mediating Variables Between Relative Deprivation and Populist Attitudes: Cases From Colombia, Peru, and Chile - Chaparro, Hernán (2024)
This research aims to analyse the indirect effect of pluralistic attitudes and political distrust on the relationship between relative deprivation and populist attitudes. We conducted a survey on a sample of 3,800 adults from Chile, Colombia, and Peru and performed a mediation analysis using structural equation modelling. The findings showed that political distrust and pluralism have positive and statistically significant indirect effects on the relation between relative deprivation and populist attitudes in these three countries. These findings suggest that perceptions of inequality may contribute to increased political distrust and be associated with pluralistic demands to listen to those perceived as marginalised from power, which ultimately predicts populist attitudes. The study posits that this is a model that may explain the inclusive populism that is often prevalent in Latin American countries. © The Author(s) 2024.